Valoración económica de los servicios ecosistémicos producto de compensaciones ambientales voluntarias por empresas del departamento del Quindío, Colombia - Garcés Upegui, Luz Deisy
The research promotes environmental conservation scenarios through a sustainable platform, with the purpose of economically valuing the Ecosystem Services (ES) resulting from voluntary environmental compensations through the implementation of Landscape Management Tools (HMP), contributing to decision making related to the allocation and prevention of anthropic impacts. The study contemplates the definition of variables, elaboration of tools, matrices and analysis of results through software. The most important ES are water supply, water regulation and connectivity of forest patches; with respect to the perception of social impacts, gender equity, the application of ancestral or traditional practices and the importance of conserving biodiversity in the properties under study are highlighted; finally, an economic valuation is established through the methods of contingent valuation and prevention, reforestation and replacement costs.